Emissivity of spinel and titanate structures aiming at the development of industrial high-temperature ceramic coatings. Issue 4 (April 2021) - Sako, E.Y.; Orsolini, H.D.; Moreira, M.; De Sousa Meneses, D.; Pandolfelli, V.C.
Abstract: High-emissivity coatings have been pointed out as a promising energy-saving solution for industrial furnaces since their development in the aerospace area. However, due to a lack of in-depth knowledge of radiation heat transfer and thermal-optical interactions, as well as the struggle to obtain proper emissivity values, commercial versions of such coatings have not yet been widely established. In this work, the evaluation of some fundamentals on thermal-optical properties, and their potential applications, led to the development of engineered structures of usual inexpensive oxides, such as the titanate and spinel ones, which presented improved emissivity values, even at high temperatures (1500 °C), when compared to commercial references. The findings of these compounds indicated a considerable cost-effective saving potential for large industrial furnaces.